EDUCATIONAL POLICIES FOR SPECIAL EDUCATION STUDENTS: WHAT RESEARCH SAYS - Espindola, Karla Franciellen Ortiz; Oliveira, Regina Tereza Cestari de (Horizontes - Revista de Educação, 2025)
This paper presents a section of the master’s research in Education, linked to the Graduate Program in Education - Master’s and Doctorate of the Catholic University of Dom Bosco (UCDB), the Research Line Policy, Management and History of Education and the Research Group on Public Policies and Education Management (GEPPE), on educational policies for people with disabilities and global developmental disorders of the Municipal Education Network of Campo Grande-MS. It aims to present a mapping of master’s dissertations in Education that discuss the theme of special and inclusive education for people with disabilities and global developmental disorders, corresponding to the years 2018 to 2023. The methodology comprises bibliographic research, through consultation of the repositories of the Catholic University of Dom Bosco (UCDB), the Federal University of Mato Grosso do Sul (UFMS) and the Federal University of Grande Dourados (UFGD). The results identified that the nine dissertations raised on the theme of special education have as a common point the analysis of the school inclusion of special education students and discuss the necessary demands for their achievement such as access, permanence, accessibility, school transportation, and available resources.